Exploring multilingual Code-Switching in Malaysia through We-Media Perspectives - Chong, Pei Qi; Ting, Hie Ling; Chan, Jie Yan; Lee, Sek Yui; Tay, Stephanie Cin Wun (Journal of Chinese Language and Culture Studies, 2023)
With the continuous development of globalization, the close contact of multiple languages has promoted the emergence of a large number of code-switching phenomena. Malaysia has the characteristics of multi-ethnic, multi-cultural and multi religious integration, which determines the phenomenon of multilingual culture in Malaysia. Malaysians use many languages to communicate. Therefore, multilingual code switching has become a unique language communication mode in Malaysia. Starting from the actual situation in Malaysia, this paper uses the video "the way Chinese speak Chinese in Malaysia" from YouTube We-Media as the research object. This paper analyzes the phenomenon of multilingual code switching in the video, analyzes and interprets its causes, so as to make a comprehensive summary of the social language phenomenon in Malaysia.